Peran Inspektorat Daerah Sebagai Watch Dog, Konsultan dan Katalis (Studi pada Pemerintah Kota Salatiga) - Kristiyani, Mita (Universitas Pendidikan Ganesha, 2020)
The task of supervising the inspectorate as an internal audit which initially played the role of a 'watchdog' is finding fault and now has a role as a consultant and catalyst. The research objectives are: to determine how the role of internal audit in the inspectorate as a watch dog, consultant and catalyst. This research is a qualitative study in which the research method used is a qualitative research method which is added qualitatively with the auditor objects in the inspectorate in the Salatiga City Inspectorate of 15 people. This type of data uses primary data obtained by distributing questionnaires and interviews. Data analysis techniques in this research are descriptive quantitative and qualitative. Research results show the role of the Inspectorate as a watchdog, especially overseeing auditee compliance with existing operational standards, conducting inspections of employee compliance with established regulations and policies and recalculating records of figures and transactions contained in financial statements. The role of the Inspectorate as a consultant is primarily to analyze all actions of OPD employees so that they do not conflict with policies, standards, procedures, laws and regulations and evaluate whether programs and operational activities are functioning properly and produce results that are in accordance with planned goals and objectives. The role of the Inspectorate as a catalyst is primarily to evaluate with the auditee the reviewed financial statements.